New MIMO Antenna with Filtration for the Future Multiuser Systems in Satellite Communications. (24th February 2022) - Essid, Chaker; Abdelhamid, Chafai; Almalki, Faris. A.; Ali, Obaid; Sakli, Hedi
Abstract : This paper emphasizes the function of the split ring resonator (SRR) within the design of ultra-wideband (UWB) antennas. We presented an antenna that belongs to the category of UWB antenna with two rejected bands based on square SRR. At first, we presented a UWB antenna. This antenna is designed to operate in the band 2.3–11.5 GHz. Then, with the integration of two SRR cells, we were capable of filtering the bands 3.7–3.9 GHz and 8.7–8.9 GHz without losing the UWB characteristics outside these rejected bands. Next, to ensure the proper performance of the MIMO system, we studied the use of metamaterials in the design of MIMO (Multiple-Input Multiple-Output) antennas for miniaturization and antenna performance.